Analysis of SARS-CoV-2 PCR and Chest CT Findings at a Single Facility in Tokyo (Machida Municipal Hospital). (30th July 2021) - Kazuyori, Taisuke; Sato, Akihito; Morimoto, Yasuhiro; Kuwano, Kazuyoshi
Abstract : Introduction . The SARS-CoV-2 reverse transcription polymerase chain reaction (RT-PCR) test is useful for diagnosing COVID-19, and the RT-PCR positive rate is an important indicator for estimating the incidence rate and number of infections. COVID-19 pneumonia is also associated with characteristic findings on chest CT, which can aid in diagnosis. Methods . We retrospectively evaluated patient background characteristics, the number of cases, the positivity rate, and chest CT findings for positive and negative cases in 672 patients who underwent RT-PCR for suspected COVID-19 at our hospital between April 3 and August 28, 2020. In addition, we compared trends in the positive rates at approximately weekly intervals with trends in the number of new infections in Machida City, Tokyo. Results . The study included 323 men and 349 women, with a median age of 46 years (range: 1 month–100 years). RT-PCR findings were positive in 37 cases, and the positive rate was 5.51%. Trends in the positive rate at our hospital and the number of new COVID-19 cases in the city were similar during the study period. Among patients with positive results, 15 (40.5%) had chest CT findings, and 14 had bilateral homogeneous GGOs. Among patients with negative results, 190 had chest CT findings at the time of examination, and 150 were diagnosed with bacterial pneumonia or bronchitis, with main findings consisting of consolidations and centrilobular opacities. Only 11 of these patients exhibited bilateral homogeneous GGOs. Conclusion . Bilateral homogeneous GGOs are characteristic of COVID-19 pneumonia and may aid in the diagnosis of COVID-19.